Phisical welfare as the indicator of the quality of nurses’ lives. Empirical study - Piotrowski, Henryk (Studia Psychologica: Theoria et praxis, 2013)
The article presents research reports covering the Mazovia region nurses’ physical welfare. The purpose of the research was to attempt at revealing and contrasting the physical welfare of the nurses and the data for Polish general population published in Social Diagnosis 2009 (Czapinski, Panek (Eds.) 2009, Conditions and quality of life of the Poles). The subject of social capital is a part of the study project conducted in 2010-2012, dedicated to multilateral analyses of the quality of life of nurses. It is an endeavor to make a diagnosis of the quality of life and individual traits of the nurses as a professional group, based on their own, subjective self-description. It had been initiated to contribute to the development of scientific thought devoted to the sources and characteristics of people’ welfare.